Pengabdian pembuatan sumur gali dalam menghindari dampak penambangan emas ilegal terhadap kesehatan masyarakat di Petapahan Kuansing - Thamrin Thamrin; Mayarni Mayarni; Viktor Amrifo; Rahmadi Rahmadi; Desfi Yunarto (PELANTAR PRESS, 2021)
Recently, gold mining has been carried out by many people in various places. The mainland Riau area can mainly be found in almost all areas of Kuansing district, but the type of mining is classified as illegal (PETI). This service is carried out in Petapan Village from July to September 2021 to prevent the community from the impact of PETI mining. To overcome this, the initiator developed dug wells as an example for the economically disadvantaged community. The dug wells that are made have clean water, not the same as some of the existing dug wells.